only: A Case Study In Projective Meaning - Craige Roberts (Baltic International Yearbook of Cognition, Logic and Communication, 2010)
I offer an integrated theory of the meaning of only in which the prejacent, while not presupposed, is both entailed and backgrounded, hence tends to project (following a general proposal about projection due to Simons et al. 2010). Moreover, I argue, contra Beaver & Brady (2008), that only is not conventionally associated with focus, the focus effects arising instead pragmatically. But I do adopt aspects of their semantics for only, including the presupposition of a pre-order over the elements of its domain.